2009
DOI: 10.1038/onc.2009.70
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 is a major effector of TrkB-mediated neuroblastoma aggressiveness

Abstract: Expression of Trk receptors is an important prognostic factor in neuroblastoma (NB) and other cancers. TrkB and its ligand brain-derived neurotrophic factor (BDNF) are preferentially expressed in NB with poor prognosis, conferring invasive and metastatic potential to the tumor cells as well as enhancing therapy resistance. Galectin-1 (Gal-1) has emerged as an interesting cancer target, as it is involved in modulating cell proliferation, cell death and cell migration, all of which are linked to cancer initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…BDNF promotes survival and proliferation of ovarian and breast cancer cells (Descamps et al 2001;Qiu et al 2006) and activates antiapoptotic pathways in lung adenocarcinomas (Perez-Pinera et al 2007). In neuroblastoma, BDNF and TrkB expression is associated with poor prognosis, increased invasiveness and metastatic potential, and enhanced therapy resistance (Cimmino et al 2009). Thus, TrkB inhibitors have been put forward as a potential anticancer therapy (Desmet and Peeper 2006;Ruggeri et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF promotes survival and proliferation of ovarian and breast cancer cells (Descamps et al 2001;Qiu et al 2006) and activates antiapoptotic pathways in lung adenocarcinomas (Perez-Pinera et al 2007). In neuroblastoma, BDNF and TrkB expression is associated with poor prognosis, increased invasiveness and metastatic potential, and enhanced therapy resistance (Cimmino et al 2009). Thus, TrkB inhibitors have been put forward as a potential anticancer therapy (Desmet and Peeper 2006;Ruggeri et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…After treatment for 72 h with CTD and NCTD at different concentrations, the metabolic activity of the treated samples was assessed as a surrogate marker for cell proliferation, using the 3-(4,5-dimethylthiazol-2-yl)-5-diphenyltetrazolium bromide (MTT; Sigma) assay, as previously described [39]. Each result is the mean ± standard deviation (SD) from six replicates, and each experiment was repeated at least three times.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Extraction of proteins from cultured cells was followed by immunoblotting with the relevant antibodies, as described elsewhere [39]. Each experiment was repeated at least three times.…”
Section: Western Blottingmentioning
confidence: 99%
“…The role of Gal-1 in molecular mechanisms leading to cancer development has been analyzed in several tumors (11) but surprisingly never in the molecular pathogenesis of HCC. In particular, it is still unknown whether Gal-1 affects the invasive ability of HCC as previously shown in other malignant tumors (25)(26)(27).…”
Section: Introductionmentioning
confidence: 98%
“…Gal-1 is a multifunctional protein involved in various aspects of tumorigenesis (cell-extracellular matrix and cell-cell interactions, cell migration, angiogenesis, tumor-immune escape) and has been described as a promising cancer target (11)(12)(13). Gal-1 expression has been examined in several malignant tumors (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and its correlation with tumor invasiveness and lymph node metastasis was demonstrated in breast cancer (25), neuroblastoma (26), oral squamous cell carcinoma and lung adenocarcinoma (27). Although Kondoh et al (28) showed that the activation of LGALS1 gene expression in HCC results from promoter hypomethylation, data on Gal-1 protein expression in HCC and its correlation to clinicopathological parameters were not available.…”
Section: Introductionmentioning
confidence: 99%